PILIHAN BAHASA DALAM MASYARAKAT MULTILINGUAL DI KEMUJAN KARIMUNJAWA JEPARA - Lailatun Niswa; Mukhlish Mukhlish (CARAKA, 2017)
The objective of this research as follows. (1) Describe the language repertory within the multilingual community in Kemujan Karimunjawa Jepara. (2) Describe domain which is the language choice within the multilingual community in Kemujan Karimunjawa Jepara. (3) Describe social variable is the determination language choice within the multilingual community in Kemujan Karimunjawa Jepara. This research included qualitative. The method research is observation method with interview technic, questioner technic, technic communication, reconded technic,  monitoring technic.  The method of analysis research is a descriptive method. The result of this research as follows. (1) Language repertory within multilingual community of Kemujan consist of (a) mostly (40%) community of Kemujan has only one language, that is BJ (20%); BB (15%); and BM (5%), (b) (30%) community of Kemujan has two languages, namely BJ and BB (10%); BJ and BI (10%); BJ and BM (5%); BB and BI (5%),  and (c) (30%) has more than two languages, those are BJ, BB, and BI (15%); BJ, BB, and BM (10%); BJ, BB, BM, and BI (5%). (2) Domain is the language choice within multilingual community of Kemujan Karimunjawa Jepara there are (a) within the family of domain, closeness/intimacy, neighbourhood, and transaction, BJ dan BB considering as the language in which mostly used, (b) within domain education, religion, and government, BJ dan BI as the language in which mostly used. (3) Social variable is determination of the language choice consist of (a) base on  the variable of education and the language in which mostly used is BJ and BI  that is (22%), (b) base on variable of job, the language in which mostly used is BJ (25%), (c) base on the gender variable, the language that mostly used is BJ (20%), and (d) base on age variable the language in which mostly used is BJ (17%).